Improving electrochemical properties of Lithium–Sulfur batteries by adding a catalyst-embedded interlayer. (20th August 2019) - Cho, Sung Ho; Cho, Sung Man; Bae, Ki Yoon; Kim, Byung Hyuk; Son, Byung Dae; Yoon, Woo Young
Abstract: To improve lithium–sulfur (Li–S) battery performance, a new interlayer film of embedded palladium cobalt (Pd3 Co) particles is developed. Pd3 Co particles on multi-walled carbon nanotubes (MWCNTs) are synthesized by using a modified polyol method. The synthesis of Pd3 Co on MWCNTs is confirmed by X-ray diffraction, transmission electron microscopy and energy-dispersive X-ray spectroscopy. The interlayer film is prepared through a filtration method using these powders. Li–S batteries with this interlayer have electrochemical properties superior to those with an MWCNT interlayer (0.2, 0.5, and 2.0 C -rates). At 0.2 and 0.5 C -rates, Pd3 Co/MWCNT-interlayer cell achieves a better performance than MWCNT-interlayer cell during 200 cycles. In addition, there is a definite performance difference for 2.0 C -rate during 300 cycles. The discharge capacities for the first and 300 cycles for the MWCNT-interlayer cell are 869 mAh g −1 and 525 mAh g −1, respectively, whereas those for a Pd3 Co/MWCNT-interlayer cell are 953 mAh g −1 and 752 mAh g −1, respectively. These improvements are resulted from the catalytic role of Pd3 Co, which assists the reaction of polysulfide formation/deformation.